Dianthus carthusianorum L. and Dianthus polonicus Zapal. in the flora of Belarus - Sautkina, Tamara A.; Patcevich, Angelina I. (Experimental Biology and Biotechnology, 2018)
The whole herbarium material collected on the territory of the Republic and identified as Dianthus carthusianorum L. underwent critical and systematical processing. It has been established that the overwhelming majority of the studied samples was presented not as D. carthusianorum L., but as Dianthus polonicus Zapal., which was not mentioned in the works of Belarusian florists before. Thus the upgrowth of D. polonicus inside Belarus was documented. The differences in formation and coloration of lemmas of both species are shown. The statistical and morphometric data concerning the length of axilla and the width of leaves as well as the size of lemmas and their awns were received. The specified features allow distinguishing between these species. Based on the herbarium labels the dot maps of the locations of D. polonicus and D. carthusianorum were made for the first time ever. It was found that D. polonicus is more widespread in Belarus than D. carthusianorum, which completely contradicts the pre-existing representations. It is suggested that the chorologic characteristics of D. polonicus and D. carthusianorum are probably determined by their belonging to carbonate soils. Both species are rare within Belarus and warrant further study.